7th Independent Science Panel Meeting, Washington DC, USA, 30-31 October 2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
In October 2014 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) held its seventh Independent Science Panel meeting in Washington DC, USA.